Factors associated with minimal changes in countermovement jump performance throughout a competitive division I collegiate basketball season - Sanders, G. J.; Boos, B.; Rhodes, J.; Kollock, R. O.; Peacock, C. O.; Scheadler, C. M. (Journal of Sports Sciences, 2019)
The purpose of the study was to assess factors that contribute to countermovement jump (CMJ) performance in women`s basketball athletes. Thirteen female athletes participated and were tested for maximal oxygen uptake (VO2max) and heart rate (HRmax). Athletes were monitored, daily for a total of 21 weeks with heart rate-based wearable devices and CMJ performance and body weight were tested weekly after one day of recovery. 3-jump average height (CMJavg), maximum height jump (CMJmax), and CMJ power (Watts) were calculated and recorded. Playing intensities >85% HRmax, HRavg, HRmax and training load were averaged for three consecutive days prior to the recovery day. After the season, data was grouped as changes in CMJ power from week one: Large (= -4.39% change), Moderate (-4.4% to -0.62% change), and Minimal (= -0.61% change) changes. Fixed-effects models revealed a main effect of group (p = 0.05) for CMJavg, CMJmax, VO2max, weekly percent changes in body weight and for 3-day training load, HRavg, and playing time at >85% HRmax. When athletes experienced minimal changes in CMJ performance, relative to large changes, they produced greater power, jumped higher, avoided negative changes in weekly body weight, had a greater preseason VO2max and 3-day average workloads appeared to have an impact on CMJ performance